Penerapan sistem e-business dan sms gateway Pada usaha sewa rumah kost di pagar alam (Studi Kasus : Kecamatan Pagar Alam Utara) - Farozi, Mohamad; Destrilia, Ririn (SISKOMTI: Jurnal Sistem Informasi Komputer dan Teknologi Informasi, 2019)
Business transaction activities that take advantage of Internet technology is part of the innovative information technology. Venture business activities undertaken by the company to enter the market in the virtual world known as electronic business (e-business) [1]. Population growth increased from time to time lead to the need for housing also increased besides efforts to improve the level of income, level of education, welfare and a better life implications for the availability of temporary residence or known as the Boarding House. Testing the interface design was done by using a questionnaire to test for errors at design time information services e-business boarding house was used and the test results, the percentage of respondents is between 50% to 74.99%, so it can be concluded that the design of information services E-business and SMS Gateway Boarding House is acceptable to be applied in providing information to the consumer (user).